The Forest as Contested Landscape in Barbara Kingsolver's Prodigal Summer. Issue 1 (2nd January 2020) - McConnell, Anne; Saladyga, Thomas
Abstract : Barbara Kingsolver's novel, Prodigal Summer, portrays conflicting perspectives on forest use and suggests that understanding and integrating different points of view can lead to more nuanced, sustainable approaches to land management. Kingsolver writes the novel from three distinct perspectives, and also stages debates between conflicting views within each narrative perspective. That narrative structure, which emphasizes multiplicity and different ways of seeing, sheds light on the dynamics of contested landscapes. While most of the criticism on the novel focuses on the setting of the farm, we turn our attention to the forest, specifically, as a landscape where different stakeholders have conflicting ideas about protection, management, and timber extraction. Each point of view, individually, displays the limitations of assessing the forest landscape from a singular vantage point, and ultimately benefits from an engagement with other ways of seeing.